Efektivitas Pemasangan Polisi Tidur (Road Humps) dalam Meningkatkan Keselamatan Lalu Lintas di Kota Bengkulu - Zefri Yedi; Rezi Munizar (Journal of Science, Technology, and Innovation, 2026)
Speed humps or speed bumps are traffic control facilities commonly implemented in residential areas to improve road user safety by reducing vehicle speed. This study aims to evaluate the conformity of speed hump dimensions and technical specifications with the provisions of Ministerial Regulation No. 14 of 2021 and to analyze their effectiveness in reducing vehicle speed in Bengkulu City. A descriptive research method was applied through field observations, physical dimension measurements, vehicle speed surveys, and community perception analysis. The results indicate that several speed humps do not comply with technical standards, particularly in terms of height, width, and marking requirements. The presence of speed humps reduces vehicle speed by 24–42%, although the resulting speed remains above the ideal limit of below 10 km/h. The findings highlight the need for proper planning, regulatory-based design implementation, and construction supervision to optimize speed hump functions while ensuring road safety and user comfort.